Weakly compact embedding of non-commutative symmetric spaces - Sadovskaya, Olga S. (E-journal of analysis and applied mathematics, 2025)
In this paper, we prove that the embeddings of certain well-known symmetric spaces are weakly compact. Our main results concern noncommutative Lorentz and Marcinkiewicz spaces on finite von Neumann algebras.